2021
DOI: 10.1128/spectrum.00105-21
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Inulin Ameliorates Subclinical Mastitis via Regulation of Rumen Microbial Community and Metabolites in Dairy Cows

Abstract: The correlation between mastitis and the gastrointestinal microbiome in dairy cows has been demonstrated. Regulating the profile of rumen microorganisms may contribute to remission of subclinical mastitis (SCM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 57 publications
(104 reference statements)
5
60
1
Order By: Relevance
“…In the current study, inulin consumption increased the Bacteroides phyla and decreased the Firmicutes phyla in the feces, which was consistent with the response of rumen microflora after inulin treatment in our previous study ( Wang et al, 2021a ). At the genus level, increased Bifidobacterium , Lachnospiraceae_NK3A20_group , as well as decreased Coprococcus and Ruminococcaceae abundances, were also identified in both feces and rumen ( Wang et al, 2021a ), suggesting several commonly modulated microbiomes between rumen and feces of dairy cows. Bacteria in the gastrointestinal tract can migrate to other niches via blood circulation ( Berg, 1995 ; Samanta et al, 2013 ; Young et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, inulin consumption increased the Bacteroides phyla and decreased the Firmicutes phyla in the feces, which was consistent with the response of rumen microflora after inulin treatment in our previous study ( Wang et al, 2021a ). At the genus level, increased Bifidobacterium , Lachnospiraceae_NK3A20_group , as well as decreased Coprococcus and Ruminococcaceae abundances, were also identified in both feces and rumen ( Wang et al, 2021a ), suggesting several commonly modulated microbiomes between rumen and feces of dairy cows. Bacteria in the gastrointestinal tract can migrate to other niches via blood circulation ( Berg, 1995 ; Samanta et al, 2013 ; Young et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…The Bacteroidetes phylum and several Firmicutes phylum produced propionate primarily via the succinate pathway, and butyrate was also a main product of the Firmicutes phylum ( Louis et al, 2014 ). Increased propionate and butyrate levels in the inulin groups were also observed in the rumen ( Zhao et al, 2014 ; Tian et al, 2019 ; Wang et al, 2021a ). Thus, in the present study, the increased norank_f_norank_o__Bacteroidales and Alistipes ( Shkoporov et al, 2015 ) in Bacteroidetes phylum might be the main contributors to the increase in propionate.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It has been suggested that the occurrence of mastitis in cows is associated with the development of SARA ( 9 ). In addition, SARA is a typical case model of rumen microflora disorder in cows, and changes in the rumen microbiota community may be associated with the development of cow mastitis ( 10 ). Recent studies have shown that the occurrence of mastitis is accompanied by changes in gut microbiota in dairy cows ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rumen microbiome directly or indirectly contributes to animal production and is susceptible to changes in feed types and components of the diet ( Kataev et al, 2020 ). The profile of the rumen microbial community and the abundance of metabolites (including the rumen fermentation index) play key roles in the health status and production performance of dairy cows ( Wang et al, 2021b ). A better understanding of the changes of rumen microbial community compositions is crucial to invest the impact of calcium propionate feed additive in dairy cows.…”
Section: Introductionmentioning
confidence: 99%